PENGEMBANGAN PENGGUNAAN MEDIA PEMBELAJARAN MATCHING ALPHABET TERHADAP KEMAMPUAN MENGENAL HURUF VOKAL ANAK USIA 4-5 TAHUN - Eriza Oktavirena Aizzalsabilla; Eka Cahya Maulidya; Kartika Rinakit Adhe; Yes Matheos Lasarus Malaikosa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and validate interactive digital learning media based on Canva called Matching Alphabet to improve the ability of 4-5 year old children in recognizing vowels. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved children in group A at Puri Cendekia Kindergarten in Surabaya, as well as subject matter experts and media experts for validity testing. The validation results showed that this media was very suitable for use, with a suitability percentage of 96.8% from subject matter experts and 90.3% from media experts. The research instrument was also declared reliable with a Cronbach's Alpha score of 0.993. Findings in the field showed that the use of the Matching Alphabet media was able to increase children's focus and enthusiasm in recognizing, naming, and distinguishing vowels (a, i, u, e, o). Thus, the Matching Alphabet media is effective as an interactive and fun basic literacy learning tool for early childhood.